2021
DOI: 10.1002/uog.21907
|View full text |Cite
|
Sign up to set email alerts
|

Planned Cesarean or planned vaginal delivery for twins: secondary analysis of randomized controlled trial

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Appropriate intrapartum conduct in a twin delivery remains a challenging aspect of obstetric practice. 3,4,19 This cohort study found that composite neonatal and maternal outcomes were superior with VD. Prior to 2013, the tendency was to deliver twins by elective CS, mainly due to the high rate of malpresentation, featuring interlocked twins, as well as the risk of acute hypoxia in the second twin from decreased placental circulation and trauma to the premature fetal brain upon passage through the birth canal.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Appropriate intrapartum conduct in a twin delivery remains a challenging aspect of obstetric practice. 3,4,19 This cohort study found that composite neonatal and maternal outcomes were superior with VD. Prior to 2013, the tendency was to deliver twins by elective CS, mainly due to the high rate of malpresentation, featuring interlocked twins, as well as the risk of acute hypoxia in the second twin from decreased placental circulation and trauma to the premature fetal brain upon passage through the birth canal.…”
Section: Discussionmentioning
confidence: 76%
“…Zamarfand et al elaborate that the impact of gestational age on composite perinatal outcome at gestations < 33 weeks as prematurity-induced morbidity may mask the effect of delivery mode compared to a term delivery. 4 The authors also discuss the protective effect that VD exerts on twins delivered at earlier gestations than 33 weeks, resulting in a lower need for mechanical ventilation. 4 A strong statistical correlation was identified between CS and neonatal intensive care unit (NICU) admission: 53.2% vs. 1.5% (p=0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations